Task-relevant spatialized auditory cues enhance attention orientation and peripheral target detection in natural scenes - Olli Rummukainen; Catarina Mendonça (Journal of Eye Movement Research)
Concurrent auditory stimuli have been shown to enhance detection of abstract visual targets in experimental setups with little ecological validity. We presented 11 participants, wearing an eye-tracking device, with a visual detection task in an immersive audiovisual environment replicating a real-world environment. The participants were to fixate on a visual target and to press a key when they were confident of having detected the target. The visual world was accompanied by a task-relevant or task-irrelevant spatialized sound scene with different onset asynchronies. Our findings indicate task-relevant auditory cues to aid in orienting to and detecting a peripheral but not central visual target. The enhancement is amplified with an increasing amount of audio lead.